THE IMPLEMENTATION OF SAVI MODEL WITH ECLIPSE CROSSWORD TO IMPROVE STUDENTS’ ACTIVITIES AND LEARNING ACHIEVEMENT OF CUBE ROOTS FOR GRADE VI SEMESTER I IN STATE ELEMENTARY SCHOOL I SANAN, GIRIMARTO DISTRICT, WONOGIRI REGENCY IN THE YEAR 2017/2018 - Samsi Suryanjani; Riyadi Riyadi; Budi Usodo (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aimed to describe the learning process, the students’ activities, and the students’ learning achievement of cube roots after the implementation of SAVI model withEclipse Crosswordfor grade VI students. Utilizing an Action Research (AR), the procedures of this study were planning, acting, observing, and reflecting. The participants were 13 students of grade VI from State Elementary School 1 in Sanan, Wonogiri in the academic year 2017/2018. The data were collected through journals of teaching and learning process, observation, post-test, and field notes, and interviews. The study revealed that the students’ activities were11.31categorized as inactive in pre-cycle, 15.54 categorized as fairly active in cycle I, and 24.85 categorized as active in cycle II.  The students’ activities also were categorized as fairly active in cycle I and active in cycle II. Mean of the students’ score had an improvement that was 57.69 with the minimum level of the learning mastery 38% in pre-cycle of grade VI in cube roots’ topics, 77.61 with the minimum level of the learning mastery 77% which had not reached the performance indicator of 80%, and 87.33 with the minimum level of the learning mastery 85% full filed the performance indicator. Therefore, the further cycle did not need to be conducted anymore. The teachers are suggested to design the lesson plan of SAVI model with Eclipse Crossword in order that the learning tools are designed well so that the students’ participation, activities, and learning achievement are above the minimum level of the learning mastery.